AUTOMATIC RECOVERY OF APPLICATION CACHE WARMTH - PARK, Kwanghyun; TELETIA, Nikhil; DO, Jae Young; PATEL, Jignesh M (2018)
The automated recovery of the warmth of cache of an application that has been subject to a running state change that degraded the warmth of the cache. To prepare for a loss in warmth, the cache portion identifiers are captured, and corresponding cache portions are stored in an external store. Thereafter, the application experiences changes in state. In order to warm the application cache more quickly, cache portions identified by the captured cache portion identifiers are retrieved from the external data store and placed in the application cache.